SIMULATIONS OF CONVECTIVE HEAT TRANSFER IN RECTANGULAR MICROCHANNEL USING THERMAL LATTICE BOLTZMANN METHOD - Bashir, Shazia; Bashir, Muhammad; Mahmoud, Khaled H.; Alsubaie, Abdulah S. A.; Afzal, Farkhanda; Alam, Mehboob; İnç, Mustafa (Vinca Inst Nuclear Sci, 2022)
The microfluidics becomes an emerging field of interest due to the advent of micro electro mechanical system. In this work simulations were performed to investigate the heat transfer phenomena in microchannel using the 2-D D2Q9 model of thermal lattice Boltzmann method. It is applicable in the whole range of slip velocity. The slip boundary condition which is combination of bounce and specular reflection was applied along with constant temperature boundary condition. For Knudson number greater than 0.001 (slip flow) fluid show slip at walls of the channel. The Reynolds number was kept at 10, Knudson Number 0.002, and aspect ratio (length/height) of 2. The fluid shows a slip of 8% of free stream velocity which is in the reported range. The resulting local Nusselt number was calculated which is responsible to quantify convective heat transfer. The simulation results were ahown to coraborate well with the analytical solution and empirical relations. Hence thermal lattice Boltzmann method satisfactorily predicted heat transfer and momentum transfer phenomena in microchannel.
Keywords: microfluidics; thermal lattice Boltzmann method; heat transfer